The ILO @ 100 Addressing the past and future of work and social protection - Gironde, Christophe; Carbonnier, Gilles; Panizza, Ugo (International Development Policy, 2019)
On the occasion of the centenary of the International Labour Organization (ILO), International Development Policy explores the Organization's progress and gaps to date and its efforts to respond to the new challenges of the fourth industrial revolution, with regard to labour and social protection. Readership: Scholars, students, academic librarians and development practitioners interested in international organisations, the ILO, the future of work, working conditions, social protection, development policy, the 4th industrial revolution, rights and social justice, the green economy, reform, child labour, migrant labour, women's labour, globalisation, automation, Asia, Africa, Europe and the informal economy.